2021
DOI: 10.3906/elk-2008-83
|View full text |Cite
|
Sign up to set email alerts
|

Using EEG to detect driving fatigue based on common spatial pattern and support vector machine

Abstract: To investigate the correlation between electroencephalogram (EEG) and driving fatigue states, this study used machine learning algorithms to detect driving fatigue based on EEG. EEG data of 14 channels were collected from thirty-four healthy subjects in this research at Northeastern University. Each subject participated in two scenarios (baseline and fatigue scenarios). Subjective ratings of fatigue levels were also obtained from the subjects using the NASA-Task Load Index (TLX). The Common Spatial Pattern (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Bu sınıflandırma algoritması, istatistiksel öğrenme teorisine dayanmaktadır. DVM'nin matematiksel algoritmaları, başlangıçta iki sınıflı doğrusal verilerin sınıflandırma problemi için tasarlanmış ve daha sonra çok sınıflı ve doğrusal olmayan verilerin sınıflandırılması için genelleştirilmiştir [25,26]. DVM tarafından üretilen doğrusal ve doğrusal olmayan hiperdüzlemler Şekil 4'te gösterilmektedir.…”
Section: Destek Vektör Makinesiunclassified
“…Bu sınıflandırma algoritması, istatistiksel öğrenme teorisine dayanmaktadır. DVM'nin matematiksel algoritmaları, başlangıçta iki sınıflı doğrusal verilerin sınıflandırma problemi için tasarlanmış ve daha sonra çok sınıflı ve doğrusal olmayan verilerin sınıflandırılması için genelleştirilmiştir [25,26]. DVM tarafından üretilen doğrusal ve doğrusal olmayan hiperdüzlemler Şekil 4'te gösterilmektedir.…”
Section: Destek Vektör Makinesiunclassified
“…This classification algorithm is based on statistical learning theory. The mathematical algorithms of SVM were originally developed for the classification problem of two-class data and then generalized for the classification of multi-class data [25]. The functional interval refers to the loss function.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…Based on the PSD features, a kernel partial least squares classifier was able to achieve 98.80% accuracy in fatigue state identification [ 7 ]. Wang et al used common spatial pattern (CSP) to extract features from 14 EEG channels and reported a 90% accuracy with support vector machine (SVM) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%